2021
DOI: 10.1093/mnras/stab3775
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the orbital period and mass relations for W UMa-type contact systems

Abstract: New relationships between the orbital period and some parameters of W Ursae Majoris (W UMa) type systems are presented in this study. To investigate the relationships, we calculated the absolute parameters of a sample of 118 systems. For this purpose, we used the parallax values obtained from the Gaia Early Data Release 3 (Gaia EDR3) star catalog for more precise calculations. The other required parameters, including the light curve solutions and the orbital period were derived from previous research. For some… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 120 publications
0
54
0
Order By: Relevance
“…(2) The result of the B − V index obtained from this work's light curves to be 0.73 ± 0.04 after calibration (Høg et al 2000) and as a result we found the effective temperature 5470 Flower (1996) study; (3) The effective temperature from the result of Poro et al (2022) analysis of the relationship between orbital period and the primary (hotter) temperature for contact systems is 5681 80) K. We chose Gaia DR2's temperature as a fixed parameter for the hotter star. In the continuation, we performed the initial light curve analysis.…”
mentioning
confidence: 57%
See 4 more Smart Citations
“…(2) The result of the B − V index obtained from this work's light curves to be 0.73 ± 0.04 after calibration (Høg et al 2000) and as a result we found the effective temperature 5470 Flower (1996) study; (3) The effective temperature from the result of Poro et al (2022) analysis of the relationship between orbital period and the primary (hotter) temperature for contact systems is 5681 80) K. We chose Gaia DR2's temperature as a fixed parameter for the hotter star. In the continuation, we performed the initial light curve analysis.…”
mentioning
confidence: 57%
“…Lindegren et al 2021;Ren et al 2021). The range of these corrections appears to include the value of observational and light curve solution uncertainties (Poro et al 2022). Therefore, in order to properly estimate the absolute parameters of the stars of AH Mic binary system, we used the Gaia EDR3 parallax method.…”
Section: Absolute Parametersmentioning
confidence: 99%
See 3 more Smart Citations